Effect of Applied Pressure During Sintering on the Densification and Mechanical Properties of SiCf/SiC Composites Prepared by Electrophoretic Infiltration - Noviyanto, Alfian (UI Scholars Hub, 2020)
SiC-fiber-reinforced SiC matrix ceramic (SiCf/SiC) composites were successfully fabricated by electrophoretic infiltration and sintering at various applied pressures. The effect of applied pressure (i.e., 5, 10, and 20 MPa) was thoroughly examined, and applied pressure appears to influence the densification and mechanical properties of SiCf/SiC composites. The densities of SiCf/SiC composites prepared at applied pressure of 5, 10, and 20 MPa were 2.99, 3.10, and 3.16 g/cm3, respectively. All samples showed dense microstructures in their matrix areas; however, many closed pores were found with increasing pressure. Pressure induced densification in the fiber area, and 20 MPa was determined to be the minimum pressure required for adequate densification. The liquid phase in the matrix area was effectively maintained at a high applied pressure, which resulted in densification. However, the liquid phase redistributed to the matrix or near the matrix area at applied pressures of MPa, leading to pores in the fiber areas of these samples. The highest flexural strength of 262 ± 18 MPa for the SiCf/SiC composite was achieved at an applied pressure of 20 MPa. Meanwhile, the flexural strengths of the composites prepared at 5 and 10 MPa were 198 ± 41 and 238 ± 32 MPa, respectively.